Prisoner for Christ - Maxwell, Stanley; Nang Chan Yeema (Nampa, ID USA Pacific Press Publishing Association, 2004)
Is based on a true story told by Pastor Robert Huang himself about how God sustained him in a Shanghai prison.
Keywords: Young Adult